2014
DOI: 10.1016/j.jspd.2014.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Is Breast Asymmetry Present in Girls with Adolescent Idiopathic Scoliosis?

Abstract: Cet article a été l'objet d'une présentation orale à la 19è conférence internationale IMAST le 11 juillet 2013 à Vancouver, CB, Canada.Le manuscrit de l'article a également été soumis à la revue scientifique de la SRS, Spine Deformity en décembre 2013. La version soumise, conforme aux normes de présentation de cette revue, est présentée aux pages suivantes. 104 ABSTRACT Study design: Cross-Sectional Descriptive StudyObjectives: To characterize breast asymmetry (BA), as defined by breast volume difference, in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Spontaneous bilateral BA is widely observed 22) . The left breast is located more caudally and is larger in female adolescents with right thoracic idiopathic scoliosis 28,34) . In Shi et al's study 31) , the incidence of BA in surgically treated female right thoracic idiopathic scoliosis is notable, with the concave breast being larger, more extroversive, and more concentrated than the convex breast.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Spontaneous bilateral BA is widely observed 22) . The left breast is located more caudally and is larger in female adolescents with right thoracic idiopathic scoliosis 28,34) . In Shi et al's study 31) , the incidence of BA in surgically treated female right thoracic idiopathic scoliosis is notable, with the concave breast being larger, more extroversive, and more concentrated than the convex breast.…”
Section: Discussionmentioning
confidence: 98%
“…Ramsay et al 28) reported a weak positive correlation between the BA and Cobb angle in girl patients with idiopathic scoliosis but also stated that the difference was statistically insignificant. The authors also found no statistically significant correlation between BA and thoracic rib hump.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In collaboration with Sainte-Justine University Hospital Centre in Montreal, Canada, MRI datasets of the trunk of 20 patients were obtained. These data were taken in the context of a study on the impact of spine deformity on breast asymmetry [41]. The datasets were acquired from adolescent girls with spine deformity.…”
Section: Trunk Test Casementioning
confidence: 99%